A Project Report on Car Automization using Protocol - SHIKHAR JYOTI DAS, SUHAIL FAYAZ AHMED, AMIT RAINA and R KUMAR (2004)
INTERNAL GUIDE: R KUMAR, TE DEPT, MVJCE EXTERNAL GUIDE: P RAMESH KUMAR, EMBEDDED SYSTEM
Keywords: Car Automization using Protocol